A Native Plant Offers Hope for Cleaner Water - Hassan, Tuan Noor Rafidah Binti Tuan (BIODIVERS - BIOTROP Science Magazine, 2025)
Freshwater ecosystems around the world are under increasing pressure from pollution, climate change, and urban development. Finding affordable and environmentally friendly ways to treat polluted water is more important than ever. A recent study has turned to nature for help; specifically, to Limnocharis flava (yellow velvetleaf), a common aquatic plant native to Malaysia. We tested this plant’s natural ability to clean water by placing it in samples from a detention pond at Politeknik Sultan Idris Shah. Over the course of nine days, Limnocharis flava caused changes in key water quality indicators, including chemical oxygen demand (COD), turbidity, pH, total suspended solids (TSS), and dissolved oxygen (DO). The results were promising. Limnocharis flava noticeably improved water quality, showing that this humble plant could be a powerful ally in low-cost, sustainable water treatment efforts; especially intropical regions where it already thrives. Interesting results, indeed. Let’s dwell further!